Rancang Bangun Aplikasi E-Arsip Pengadaan Tanah dalam Mendukung Pengelolaan Pertanahan Daerah - Jauhari, Mahfud; Rahmawati, Ika; Daniswari, Alfiani Putri; Rahmadini, Lisdiana; Rineksi, Trisnanti Widi (Widya Bhumi, 2025)
The use of information technology in public services, especially in local government agencies in the land sector, has a positive impact on administrative efficiency. This study focuses on the implementation of a digital archive system for managing land acquisition documents at the Yogyakarta City Land and Spatial Planning Service. Conventional methods that have been used so far have caused various problems, including process inefficiencies, document security vulnerabilities, and difficulties in tracking archives. To overcome these problems, an E-Archive application was developed by implementing the Waterfall system development model consisting of the following stages: (1) needs analysis, (2) system design, (3) implementation, (4) testing, and (5) maintenance. This system was built using the PHP programming language for the backend and CSS for the frontend. The results of black box testing showed that all system functions operated according to the specified requirements. The implementation of this system succeeded in increasing data accessibility by 40% and reducing administrative workload by 35%. This study not only presents technical solutions for archive digitization but also provides a digital transformation model that can be adopted by other local government agencies. Pemanfaatan teknologi informasi dalam pelayanan publik, khususnya di instansi pemerintah daerah bidang pertanahan, memberikan dampak positif terhadap efisiensi administrasi. Penelitian ini berfokus pada implementasi sistem arsip digital untuk pengelolaan dokumen pengadaan tanah di Dinas Pertanahan dan Tata Ruang Kota Yogyakarta. Metode konvensional yang selama ini digunakan menimbulkan berbagai masalah, termasuk inefisiensi proses, kerentanan keamanan dokumen, dan kesulitan dalam pelacakan arsip. Untuk mengatasi masalah tersebut, dikembangkan aplikasi E-Arsip dengan menerapkan model pengembangan sistem Waterfall yang terdiri dari tahap: (1) analisis kebutuhan, (2) perancangan sistem, (3) implementasi, (4) pengujian, dan (5) pemeliharaan. Sistem ini dibangun menggunakan bahasa pemrograman PHP untuk backend dan CSS untuk frontend. Hasil pengujian black box menunjukkan seluruh fungsi sistem beroperasi sesuai dengan persyaratan yang ditetapkan. Implementasi sistem ini berhasil meningkatkan aksesibilitas data sebesar 40% dan mengurangi beban kerja administratif hingga 35%. Penelitian ini tidak hanya menyajikan solusi teknis untuk digitalisasi arsip, tetapi juga memberikan model transformasi digital yang dapat diadopsi oleh instansi pemerintah daerah lainnya.